Canonical correlations between agronomic traits and seed physiological quality in segregating soybean populations - Pereira, E. M. [UNESP]; Silva, F. M. [UNESP]; Val, B. H. P. [UNESP]; Pizolato Neto, A. [UNESP]; Mauro, A. O. [UNESP]; Martins, C. C. [UNESP]; Uneda-Trevisoli, S. H. [UNESP] (Funpec-editora, 2017)
The objective of this study was to evaluate the relationship between agronomic traits and physiological traits of seeds in segregating soybean populations by canonical correlation analysis. Seven populations and two commercial cultivars in three generations were used: F-3 plants and F-4 seeds; F-4 plants and F-5 seeds, and F-4 seeds and plants. The following agronomic traits (group I) were evaluated: number of days to maturity, plant height at maturity, insertion height of first pod, number of pods, grain yield, and oil content. The physiological quality of seeds (group II) was evaluated using germination, accelerated aging, emergence, and emergence rate index tests. The results showed that agronomic traits and physiological traits of seeds are not independent. Intergroup associations were established by the first canonical pair for the generation of F-3 plants and F-4 seeds, especially between more productive plants with a larger pod number and high oil content and seeds with a high germination percentage and emergence rate. For the generation of F-4 plants and F-5 seeds, the first canonical pair indicated an association between reduced maturity cycle, seeds with a high emergence percentage and a high percentage of normal seedlings after accelerated aging. According to the second canonical pair, more productive and taller plants were associated with seed vigor. For the generation of F-4 seeds and plants, the associations established by the first canonical pair occurred between seed vigor and more productive plants with high oil content and reduced maturity cycle, and those established by the second canonical pair between seeds of high physiological quality and tall plants.
Keywords: Multivariate analysis; Associations between traits; Glycine max; Seed quality